Climate change patterns in Amazonia and biodiversity - Cheng, Hai J.; Sinha, Ashish; Cruz, Francisco W.; Wang, Xianfeng; Edwards, R.; D'Horta, Fernando Mendonça; Ribas, Camila Cherem; Vuille, M.; Stott, Lowell D.; Auler, Augusto Sarreiro (Nature Communications, 2013)
Precise characterization of hydroclimate variability in Amazonia on various timescales is critical to understanding the link between climate change and biodiversity. Here we present absolute-dated speleothem oxygen isotope records that characterize hydroclimate variation in western and eastern Amazonia over the past 250 and 20 ka, respectively. Although our records demonstrate the coherent millennial-scale precipitation variability across tropical-subtropical South America, the orbital-scale precipitation variability between western and eastern Amazonia exhibits a quasi-dipole pattern. During the last glacial period, our records imply a modest increase in precipitation amount in western Amazonia but a significant drying in eastern Amazonia, suggesting that higher biodiversity in western Amazonia, contrary to 'Refugia Hypothesis', is maintained under relatively stable climatic conditions. In contrast, the glacial-interglacial climatic perturbations might have been instances of loss rather than gain in biodiversity in eastern Amazonia, where forests may have been more susceptible to fragmentation in response to larger swings in hydroclimate. © 2013 Macmillan Publishers Limited. All rights reserved.
Keywords: Oxygen; Biodiversity; Climate Change; Climate Conditions; Fragmentation; Glacial-interglacial Cycle; Last Glacial; Nature-society Relations; Oxygen Isotope; Precipitation (climatology); Speleothem; Time-scale; Biodiversity; Climate; Climate Change; Forest; Glacial Period; Hypothesis; Precipitation; South America; Cave; El Nino; Geography; Time; Amazonia; Biodiversity; Caves; Climate Change; El Nino-southern Oscillation; Geography; Oxygen Isotopes; South America; Time Factors